Political engagement among students in UiTM Shah Alam / Alma Mustaza Mohd Suhaimi - Mohd Suhaimi, Alma Mustaza (2019)
This study aims to measure the level of political engagement among the students in UiTM Shah Alam. In Malaysia political landscape, the involvement of youth had been increased. Even though they were restricted by the University and University College Act, they resisted to stop. The purpose of this study is to identify the factors that contribute to the political engagement of the students. By using the quantitative method, the questionnaires were distributed to the 380 respondents who are the students of UiTM Shah Alam. Descriptive analysis, Pearson Correlation and Multiple Regression were used to achieve the research objective. Thus, this study found that the level of political engagement among the students in UiTM Shah Alam is moderate. Furthermore, there is relationship between parental influence, peer influence, social media influence, educational environment and political engagement among the students in UiTM Shah Alam. In addition, this study found that the most influential factor is the peer influence. Unlike the previous studies, most of the studies found the social media as the most influential factor due to the fast pace of information delivery through the social media nowadays. Finally, this study can be extended to cover a wider group of youth in Malaysia.